Scriptures and the guidance of language evaluating a religious authority in communicative action - Smith, Steven G. 1957- (Cambridge University Press, 2018)
"In this book, Steven G. Smith focuses on the guidance function in language and scripture and evaluates the assumptions and ideals of scriptural religion in global perspective. He brings to language studies a new pragmatic emphasis on the shared modeling of life-in-the-world by communicators constantly depending on each other's guidance. Using concepts of axiality and axialization derived from Jaspers' description of the "Axial Age," he shows the essential role of scripture in the historical progress of communicative action. This volume clarifies the formative power of scriptures in religions of the "world religion" type and brings scripture into philosophy of religion as a major cross-cultural category of study, thereby helping philosophy of religion find a needed cross-cultural footing" ...
Includes bibliographical references and index
Keywords: Language and languages -- Religious aspects; Sacred books; Religiöse Sprache; Kommunikation; Heilige Schrift; Autorität